2015
DOI: 10.1136/flgastro-2015-100594
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment in acute non-variceal upper GI bleeding: the AIMS65 score in comparison with the Glasgow–Blatchford score in a Scottish population

Abstract: Introduction The early use of risk stratification scores is recommended for patients presenting with acute non-variceal upper gastrointestinal (GI) bleeds (ANVGIB). AIMS65 is a novel, recently derived scoring system, which has been proposed as an alternative to the more established Glasgow-Blatchford score (GBS). Objective To validate the AIMS65 scoring system in a predominantly Caucasian population from Scotland and compare it with the GBS. Design Retrospective study of patients presenting to a district gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The AIMS65 score has been advocated as an even simpler score requiring scoring only on a 5-point score for each of the following factors: albumin of less than 30 g/l, international normalised ratio (>1.5), Glasgow coma scale score of less than 14, systolic blood pressure of less than 90 mmHg, and age of more than 65. Although the AIMS65 can reliably predict mortality, it appears less accurate than the GBS in determining the need for interventions such as blood transfusion or admission to critical care 15 , 16 .…”
Section: Risk Stratificationmentioning
confidence: 99%
“…The AIMS65 score has been advocated as an even simpler score requiring scoring only on a 5-point score for each of the following factors: albumin of less than 30 g/l, international normalised ratio (>1.5), Glasgow coma scale score of less than 14, systolic blood pressure of less than 90 mmHg, and age of more than 65. Although the AIMS65 can reliably predict mortality, it appears less accurate than the GBS in determining the need for interventions such as blood transfusion or admission to critical care 15 , 16 .…”
Section: Risk Stratificationmentioning
confidence: 99%
“…Although the AIMS65 can reliably predict mortality, it appears less accurate than the GBS in determining the need for interventions such as blood transfusion or admission to critical care. 15,17 A further score, the Progetto Nazionale Emorragia Digestive score (PNED) system which relies on a rather cumbersome multipart scoring utilising age, the presence of cancer, renal failure, American Society of Anaesthesiologists (ASA) grade, cirrhosis, rebleeding and failure of endoscopic therapy has been proposed. A large prospective study of over 3000 patients confirmed that the GBS clearly performed best in identifying the lowest risk patients and also in predicting important interventions such as endoscopic therapy or blood transfusion.…”
Section: Risk Stratificationmentioning
confidence: 99%
“…Although the AIMS65 can reliably predict mortality, it appears less accurate than the GBS in determining the need for interventions such as blood transfusion or admission to critical care. 15,17…”
Section: Risk Stratificationmentioning
confidence: 99%
“…However, criticism of the GBS has arisen from its complexity. Palmer and colleagues,1 in this edition of Frontline Gastroenterology (FG) have compared the GBS with a simpler non-endoscopic score, the AIMS65. This 5-point score was found to be superior to GBS in predicting 30-day mortality, but not transfusion requirement.…”
Section: What's the Score: Risk Assessment In Upper Gastrointestinal mentioning
confidence: 99%